P347 Practical recommendations for the collection of the patient-reported outcomes included in the Health Outcomes Observatory (H2O) core data set for patients with inflammatory bowel disease. (30th January 2023) - Fierens, L; Casellas, F; Borruel, N; van der Woude, C J; Huberts, A S; Siegmund, B; Sonnenberg, E; Novacek, G; Gerold, N; Stamm, T; Hedin, C R; Julsgaard, M; et al.
Abstract: Background: Large scale data integration and comparison require standardised data collection. As part of the Health Outcomes Observatory (H2O) project, a core data set for IBD (including case-mix variables, biomarkers, clinical and patient-reported outcomes) that can uniformly be implemented across IBD centres was defined through an international, multi-stakeholder Delphi process. The next step was to identify the most appropriate instruments and minimum frequency to measure the patient-reported outcomes included in this core data set. Fierens L et al, UEG Week 2022. Methods: A group of key stakeholders assessed potential instruments that were identified through a literature review. The literature review report included details on the development process, validation studies, extensiveness, required licenses and available translations of the identified instruments. The stakeholders were then asked to indicate in a survey which instrument(s) they considered most important to include in the core data set and at what minimum frequency they would collect these data. The collected insights were discussed at an online consensus meeting in Sept 2022 where a final selection of instruments and minimum frequency was agreed on. Results: In total, 18 stakeholders from 10 different countries completed the survey (7 IBD specialists, 4 patient advocates, 3 pharma experts, 2 IBD nurses, 1 expert in patient-reported outcome measurements and 1 regulator). Also 18 stakeholders attended the consensus meeting (6 IBD specialists, 5 patient advocates, 3 academic researchers, 3 pharma experts and 1 IBD nurse from 11 different countries). The PRO-2 (both for UC and CD) and the IBD-Control were indicated as the most appropriate instruments to collect the IBD-specific outcomes, and the PROMIS Global Health and PROMIS Self-Efficacy short form to collect the generic patient-reported outcomes. At the consensus meeting it was additionally agreed to use the generic Health Monitor (disease acceptance and control) and to supplement the set with additional single items to measure bowel incontinence, bowel urgency, IBD medication adherence and the extent to which patients feel informed (Figure). It was agreed that the IBD-specific outcomes would be collected at every consultation with an IBD practitioner, and generic outcomes every 12 months. Conclusion: This study recommends an instrument set and minimum frequency to measure the patient-reported outcomes included H2O core data set for IBD, agreed on by a group of key stakeholders. This set will initially be implemented in five European university clinics and subsequently in additional IBD clinics, enabling data integration and comparisons on a larger scale.